Neumann-Robin problem for p(x)-Laplacian equations in a domain with the boundary edge - Mikhail Borsuk (Electronic Journal of Differential Equations)
We investigate the behavior of weak solutions to the mixed problem with Neumann and Robin boundary conditions for an elliptic quasi-linear second-order equation with the variable $p(x)$-Laplacian in a neighborhood of the boundary edge.